ESTUDO DO ÁCIDO PERACÉTICO NA DESINFECÇÃO DE ESGOTO SANITÁRIO: INFLUÊNCIA DAS CARACTERÍSTICAS FÍSICO-QUÍMICAS DO EFLUENTE, DETERMINAÇÃO DE CONCENTRAÇÃO RESIDUAL E CINÉTICA DE DEGRADAÇÃO - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
This work aims to study the use of peracetic acid (PAA) to disinfect wastewater. Into this perspective, some methods were investigated to determine residual PAA, factors that interfere with its disinfecting action, its kinetic of degradation in wastewater and some possible by-products coming from its application. The results showed that the concentrations between 0,5 and 10 mg/L of PAA could be determined as for cerimetric/iodometric method as for spectrofotometric method using cromophore DPD. To concentrations between 01 and 05 mg/L only the method with DPD could be recommended. The disinfection tests with PAA demonstrated the grades of SST larger than 50mg/L implicated in an increase of 50% in disinfectant consume to inactivate total coliforms microorganisms and E.coli. The efficiency to inactivation of PAA related to the E.coli was also damaged in conditions of pH larger than 8. The time of contact had major influence in disinfection efficiency in dose up to 5mg/L of PAA. The kinetic tests showed that the degradation of PAA, about the studied wastewater, could be represented for a reaction of first order and its time of half-life in the wastewater was estimated in 79 minutes. The formation of by-products: nonanal, decanal, chlorophenols and 1-metoxi-4-methylbenzene weren’t observed in the wastewater, using the PAA dose of 10mg/L. With this same dose the physicochemical conditions like pH, BOD and COD of wastewater didn’t suffer prominent variation, however the DO got a larger increase of 60%, being this one of the most significant physicochemical contributions. Thus, the results with application of PAA indicated that its use in doses up to 10mg/L contributed to inactivate microorganisms and not altered significantly initial conditions of wastewater and there weren’t environmental damages demonstrated about the studied parameters.
Keywords: ácido peracético; desinfecção de efluente sanitário; cinética de degradação; peracetic acid; disinfection of the wastewater; kinetic of degradation; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA